Physiological Responses of Red Tilapia (Oreochormis niloticus) to Photoperiod - Ahmad Wiranda; Khusnul Khotimah; Meika Puspita Sari; Elva Dwi Harmilia; Irkhamiawan Ma'ruf (Universitas Muhammadiyah Palembang, 2025)
Environmental factors play an important role in the growth and survival of fish, both directly and indirectly. This role is not limited to determining the success of fish growth in terms of length and weight; fish behavior, feeding patterns, and metabolism are also affected. Photoperiod itself is defined as the length of time of light and dark exposure. This study aims to evaluate the effect of photoperiodism on the growth rate and physiological response of red tilapia (Oreochromis niloticus). The study was conducted in Gandus District, Palembang City. Data and analysis were performed using a completely randomized design (CRD) with several parameters such as growth rate, weight gain, survival rate, and behavior of red tilapia observed qualitatively in response to treatment with varying light exposure times. The treatments given were 3 variations of light and dark exposure and 5 repetitions with variations P1: 20 hours of light: 4 hours of dark (20T; 4G) P2: 16 hours of light: 8 hours of dark (16T; 8G), and P3: 12 hours light : 12 hours dark (12T; 12G). The analysis results showed that red tilapia had a positive growth response, characterized by an increase in fish length and weight, caused by increased metabolism due to an increase in feed consumption rate. Fish behavior changed compared to the control group due to physiological stress caused by prolonged exposure to light.